Copy of a despatch from Her Majesty's minister at Washington inclosing a treaty between Her Majesty and the United States of America for arbitration concerning the seal fisheries in Behring's Sea [electronic resource]. - Pauncefote, Julian Pauncefote, Baron, 1828-1902.; United States 1892 Feb. 29. Treaties, etc. Great Britain,U; Great Britain 1892 Feb. 29. Treaties, etc. United States,n (London : Printed for H.M.S.O. by Harrison, 1892)
Signed: Julian Pauncefote. Original issued in series: [Command papers / Great Britain. Parliament] Cd. 6634. At head of title: United States. No. 2 (1892). "Presented to both Houses of Parliament by Command of Her Majesty. March, 1892." Electronic reproduction. Mode of access: Internet. 44